Rapid Genome Engineering of Pseudomonas Assisted by Fluorescent Markers and Tractable Curing of Plasmids - Daniel C. Volke; Nicolas T. Wirth; Pablo Ivan Nikel (Bio-Protocol, 2021)
Precise genome engineering has become a commonplace technique for metabolic engineering. Also, insertion, deletion and alteration of genes and other functional DNA sequences are essential for understanding and engineering cells. Several techniques have been developed to this end (e.g., CRISPR/Cas-assisted methods, homologous recombination, or λ Red recombineering), yet most of them rely on the use of auxiliary plasmids, which have to be cured after the editing procedure. Temperature-sensitive replicons, counter-selectable markers or repeated passaging of plasmid-bearing cells have been traditionally employed to circumvent this hurdle. While these protocols work reasonably well in some bacteria, they are not applicable for other species or are time consuming and laborious. Here, we present a fast and versatile protocol of fluorescent marker-assisted genome editing in Pseudomonas putida, followed by clean curing of auxiliary plasmids through user-controlled plasmid replication. One fluorescent marker facilitates identification of genome-edited colonies, while the second reporter enables detection of plasmid-free bacterial clones. Not only is this protocol the fastest available for Pseudomonas species, but it can be easily adapted to any type of genome modifications, including sequence deletions, insertions, and replacements.Graphical abstract:Rapid genome engineering of Pseudomonas with curable plasmids